The Role of Female Members of The Regional People's Representative Council (DPRD) in Addressing Gender Issues in The City of Palembang - Ocin Permatasari; Kun Budianto; Siti Anisyah (Jurnal Studi Sosial dan Politik, 2025)
This study aims to identify and analyze the role of female members of the Regional Representative Council (DPRD) in addressing gender issues, particularly gender-based violence against women in Palembang City during the 2024-2029 term. The analysis was conducted using Hanna Fenichel Pitkin’s theory of Political Representation, with a focus on substantive representation (acting for). The research method employed was a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews with female DPRD members and representatives from the Department of Women’s Empowerment and Child Protection (DPPPA), as well as document analysis. The research findings indicate that the role of female DPRD members in responding to the surge in gender-based violence cases in Palembang City has gone beyond the bounds of formal representation. This role is demonstrated through three main dimensions. First, political accountability is built through emotional closeness with women’s organizations and grassroots communities to integrate their aspirations into the local policy agenda. Second, responsiveness is manifested through intuitive sensitivity rooted in shared experiences as women, enabling them to take the initiative and create safe spaces for victims of violence. Third, effectiveness is demonstrated by optimizing technocratic interventions through oversight of local regulation drafts to ensure they are free from gender bias, monitoring gender budgeting, and fostering cross-sectoral collaboration with the DPPPA. Overall, these findings confirm that the presence of women in the legislature is not merely about fulfilling quotas, but rather about serving as agents of change who break down patriarchal barriers through a combination of emotional closeness, swift responsiveness to marginalized issues, and the courage to intervene in technocratic processes.